New method for the identification of arbuscular mycorrhizal fungi by proteomic-based biotyping of spores using MALDI-TOF-MS. Issue 1 (December 2017) - Crossay, Thomas; Antheaume, Cyril; Redecker, Dirk; Bon, Lucie; Chedri, Nicolas; Richert, Clément; Guentas, Linda; Cavaloc, Yvon; Amir, Hamid
Abstract Arbuscular mycorrhizal fungi (AMF, Glomeromycota) are mutualistic symbionts associated with majority of land plants. These fungi play an important role in plant growth, but their taxonomic identification remains a challenge for academic research, culture collections and inoculum producers who need to certify their products. Identification of these fungi was traditionally performed based on their spore morphology. DNA sequence data have successfully been used to study the evolutionary relationships of AMF, develop molecular identification tools and assess their diversity in the environment. However, these methods require considerable expertise and are not well-adapted for "routine" quality control of culture collections and inoculum production. Here, we show that Matrix-Assisted Laser Desorption Ionisation Time of Flight Mass Spectrometry proteomic-based biotyping is a highly efficient approach for AMF identification. Nineteen isolates belonging to fourteen species, seven genera and five families were clearly differentiated by MALDI biotyping at the species level, and intraspecific differentiation was achieved for the majority. AMF identification by MALDI biotyping could be highly useful, not only for research but also in agricultural and environmental applications. Fast, accurate and inexpensive molecular mass determination and the possibility of automation make MALDI-TOF-MS a real alternative to conventional morphological and molecular methods for AMF identification.